2006
DOI: 10.1128/mcb.01845-05
|View full text |Cite
|
Sign up to set email alerts
|

Shared Stabilization Functions of Pyrimidine-Rich Determinants in the Erythroid 15-lipoxygenase and α-globin mRNAs

Abstract: The poly(C)-binding proteins, ␣CPs, comprise a set of highly conserved KH-domain factors that participate in mRNA stabilization and translational controls in developmental and viral systems. Two prominent models of ␣CP function link these controls to late stages of erythroid differentiation: translational silencing of 15-lipoxygenase (Lox) mRNA and stabilization of ␣-globin mRNA. These two controls are mediated via association of ␣CPs with structurally related C-rich 3-untranslated region elements: the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…No modification of hnRNP E1 has been reported that attenuates its binding to the DICE. Of note, there has been one contrasting report in which translational silencing of DICE-containing reporter constructs was not observed in HeLa cells (Kong et al 2006), even though the cellular context was not well defined in the reported studies.…”
Section: Translational Regulationmentioning
confidence: 65%
“…No modification of hnRNP E1 has been reported that attenuates its binding to the DICE. Of note, there has been one contrasting report in which translational silencing of DICE-containing reporter constructs was not observed in HeLa cells (Kong et al 2006), even though the cellular context was not well defined in the reported studies.…”
Section: Translational Regulationmentioning
confidence: 65%
“…Pcbp2 has been mechanistically linked to both nuclear and cytoplasmic posttranscriptional controls over globin gene expression (20,36,63). The in vivo role of Pcbp2 in hematopoiesis was facilitated by the fact that Pcbp2-null embryos remain uniformly viable at 12.5 dpc, a developmental time point where hematopoiesis is well established in the fetal liver.…”
Section: Contrast Pcbp2mentioning
confidence: 99%
“…Real-time PCR confirmed the enrichment of the 9 RNA species in the BAP-PCBP2-associated population compared with the BAP-GFP control ( Figure 4C). In many cases, PCBP2 functions through binding to the 3′ untranslated region (UTR) or 5′ UTR of its target mRNAs (6,32). Defined PCBP2 binding sites contain short patches of C-or CU-rich sequences (25,33).…”
Section: Figurementioning
confidence: 99%